Nomenclatural notes on the taxonomic identity of Sprengel’s Erigeron dubius, E. montevidensis, E. resinosus and E. filiformis (Asteraceae) - Moraes, Pedro Luís Rodrigues De (Phytotaxa, 2020)
The names Erigeron dubius, E. montevidensis, E. resinosus, and E. filiformis (Asteraceae) are investigated. Specimens from Kurt Sprengel’s private herbarium, kept at the Paris Herbarium (P), are designated as lectotypes. Erigeron dubius and E. resinosus are currently recognized under Hysterionica, whereas E. montevidensis and E. filiformis are treated under Neja. Based on the original material, Erigeron dubius and E. resinosus are proposed as new heterotypic synonyms of Hysterionica nidorelloides, having equal nomenclatural priority over the latter, therefore I here propose a nomenclatural transfer as Hysterionica resinosa comb. nov. (≡ E. resinosus). Erigeron montevidensis is proposed as a new heterotypic synonym of Neja filiformis, whose basionym is E. filiformis. Additionally, lectotypes for the names Neja gracilis and N. linearifolia are designated.